1995
DOI: 10.1182/blood.v86.10.3660.bloodjournal86103660
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal primitive hematopoietic progenitors can be detected in mobilized peripheral blood from patients with high-risk myelodysplastic syndromes

Abstract: Myelodysplastic syndromes (MDS) form a heterogeneous group of clonal hematopoietic disorders with unfavourable prognosis. Allogeneic bone marrow transplantation is the only potentially curative treatment, but remains limited to a small subgroup of younger patients with HLA- compatible donors. As autologous stem cell transplantation is currently being explored as an alternative treatment strategy for MDS, more information needs to be acquired regarding the clonal nature of the progenitor cells in these autograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Three patients with a normal to excellent PBPC yield (nos. 5, 6 and 9) were demonstrated to be polyclonal by techniques based on X-chromosome inactivation (PCR analysis with the HUMARA probe) (Delforge et al, 1995). Other investigators confirmed in in vitro experiments, using the same X-linked probe, the possibility to culture polyclonal progenitors in patients with established MDS (Anan et al, 1995).…”
Section: Discussionmentioning
confidence: 84%
“…Three patients with a normal to excellent PBPC yield (nos. 5, 6 and 9) were demonstrated to be polyclonal by techniques based on X-chromosome inactivation (PCR analysis with the HUMARA probe) (Delforge et al, 1995). Other investigators confirmed in in vitro experiments, using the same X-linked probe, the possibility to culture polyclonal progenitors in patients with established MDS (Anan et al, 1995).…”
Section: Discussionmentioning
confidence: 84%
“…Chemotherapy induces cytogenetically normal CRs in the majority of patients (de Witte et al, 1995). In addition, the peripheral stem cell harvests of three patients with MDS appeared to be polyclonal, when assessed by polymerase chain reaction (PCR) techniques based on X-chromosome inactivation patterns (Delforge et al, 1995). Preliminary data indicate that repopulation after transplantation with mobilized peripheral stem cells was much faster than autologous bone marrow transplantation (Carella et al, 1996;Demuynck et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Mobilization of peripheral blood stem cells (PBSC) offers an alternative in such cases. Furthermore, peripheral stem cell transplants in MDS patients are capable of restoring sustained polyclonal haemopoiesis after high-dose chemotherapy (Delforge et al, 1995;Demuynck et al, 1996), and offer the additional potential advantage of more rapid and complete haemopoietic reconstitution when compared to ABMT . Our study demonstrates the feasibility of stem cell collection and subsequent autologous transplantation following FLAG-idarubicin chemotherapy.…”
Section: Discussionmentioning
confidence: 99%